2008
DOI: 10.2131/jts.33.641
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of rapeseed oil as the sole fat nutrient in wistar rats - Lack of increase in plasma lipids and renal lesions -

Abstract: INTRODUCTIONLow erucic acid rapeseed (canola) oil (CO) has been reported to shorten survival times in stroke-prone spontaneously hypertensive rats (SHRSP), compared with rats given soybean oil (SO), when each oil was added at 10 w/w% to standard rat chow (Huang et al., , 1997Miyazaki et al., 1998). Previous studies suggested that CO ingestion shortens the life of SHRSP via an acceleration of hypertension-related conditions, including elevation of blood pressure and tissue lesions in the kidney and heart (Naito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
(36 reference statements)
1
3
0
Order By: Relevance
“…In the present work, Wistar-Han rats fed a 20 % rapeseed oil diet for 33 days did not show altered biochemical plasma markers or internal lesions, in agreement with previous studies (Ohara et al 2008). Extra attention was given to the hearts of these animals, which showed increased weight in relation to total animal weight (Table S3).…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, Wistar-Han rats fed a 20 % rapeseed oil diet for 33 days did not show altered biochemical plasma markers or internal lesions, in agreement with previous studies (Ohara et al 2008). Extra attention was given to the hearts of these animals, which showed increased weight in relation to total animal weight (Table S3).…”
Section: Discussionsupporting
confidence: 92%
“…If such a condition were ubiquitous in organs other than the testis, it is possible that dietary hydrogenated soybean oil and canola oil would cause a relative predomination of mineralocorticoid synthesis over sex hormone synthesis. In this context, it should be noted that in Wistar rats fed a canola oil diet, the serum aldosterone level was significantly higher, by 30%, than in those fed a soybean oil diet (Ohara et al, 2008) and that a similar change was also found in SHRSP given canola oil . Aldosterone plays a crucial role in the cause and exacerbation of vascular injury accompanied with hypertension (Schiffrin, 2006).…”
Section: Discussionmentioning
confidence: 73%
“…Previously it was found that the plasma aldosterone level was significantly higher in male Wistar rats fed a CAN diet for 10 weeks than in animals fed a SOY diet [ 50 ]. Moreover, it was also found that testosterone levels in the testis and plasma in SHRSP were significantly decreased after ingestion of a CAN diet for 12 weeks, compared to the control animals given a SOY diet [ 12 ].…”
Section: Discussionmentioning
confidence: 99%